IMPLEMENTASI KURIKULUM 2013 (TERPADU) DI RA BAITURRAHMAN BIMA CIREBON - Khairunnisa Ulfadhilah; Nurlaela; Sukiman (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2021)
The curriculum is an important foundation in the learning process at RA Baiturrahman Bima Cirebon which starts from planning to assessment. Curriculum development tailored to the needs of society and child-oriented. The purpose of this study was to determine the implementation development of the 2013 curriculum. The method used in this study used a descriptive qualitative approach. The data collection techniques used in this study used observation to see firsthand the implementation of the 2013 curriculum, interviews to obtain more valid information, and documentation. The data analysis technique in this observation is using the data reduction model of Miles and Huberman in order to retrieve the actual data and this research uses the triangulation technique to test the validity of the data that has been obtained.